Promoting community engagement in sustainable ecotourism development planning in protected areas the case of Naujan Lake Natural Park - Brion, Juliepearl P.; Regunay, Jose M. (Quezon City School of Urban and Regional Planning, University of the Philippines Diliman, 2018)
Community engagement has been a thrust of modern tourism development principle. In ecotourism, engagement of communities from planning, implementation until evaluation is vital to ensure that any development would be sustainable. However, it is easier said than done. This research aims to promote community engagement as a vital tool for a sustainable ecotourism development planning in a protected area by looking at the management approach and strategies employed towards ecotourism development. Specifically, it looks at the level of community engagement employed in the management of ecotourism in Naujan Lake Natural Park, assesses the management strategies employed for engaging communities, and determines its implications in sustainable ecotourism development and the factors that facilitate or hinder community engagement efforts. These are done through cross validation of the results of household survey, key informant interviews, focus group discussion, secondary data review and site visits and assessments. For Naujan Lake Natural Park, the formula for a thriving and sustainable ecotourism is there -the DENR which employs the government-mandated policies in the conservation and protection of NLNP; the PAMB that manages any activity and program inside the NLNP community, the support of the academe in the continuous research and community engagement services, and the support of other stakeholders of NLNP. Nonetheless, the community does not see itself as actively engaged in ecotourism for the reason that ecotourism in NLNP is not a priority as a program of sustainable protected area management. Community engagement is present in existing conservation programs but for Bangklase-an ecotourism program where tourists experience lake cruising while attending lectures onboard about the Naujan Lake and other vital issues on environmental protection and conservation-the community does not see itself as actively engaged in the program. They only know that there is Bangklase but they are uncertain where the tour operator comes from. Furthermore, no one even discusses about the bird watching activities in the lake which is another ecotourism activity. It only shows that they were not engaged in the said ecotourism activities in NLNP. In so far as ecotourism management is concerned, community engagement is on its infantile stage. This could be attributed to the fact that, tourism development as a whole and ecotourism in particular, may have not been sufficiently promoted as a tool for protected area management and conservation. Although there is a significantly positive attitude towards ecotourism in the lake, much has to be realized as far as the actual management of an existing ecotourism activity is concerned. In the pursuit of sustainability, the paper shows that in order to sustain ecotourism development in the protected area; the community must have shared benefits and responsibilities. This is demonstrated by the community's agreeable attitude in having economic activities in the lake while still being supportive of conservation efforts. There is, thus, the need to support ecotourism as a tool for protected area management and conservation. And to effectively achieve sustainable ecotourism development, the engagement of the community must be in place to facilitate the co-management and co-ownership of ecotourism activities in protected area.
Thesis (M.A. Urban and Regional Planning)--University of the Philippines Diliman
Keywords: National parks and reserves -- Philippines -- Mindoro; Protected areas -- Philippines -- Mindoro; Ecotourism -- Philippines -- Mindoro